Fabrication And Investigation Of Al-Doped Zno Nanorods For Laser-Based Temperature Sensor Applications - Azmi, Atiqah Nabieha (2024)
This work highlights the potential of random lasers as thermal laser-based sensor at room temperature within the uv-range. The work includes synthesis of zno nanorods, doping the zno, measuring the lasing, and laser-based sensing parameters. The zno nanorods were synthesized on glass substrate using chemical bath deposition (cbd) method for three hours at 96 °c and revealed an average nanorod height and diameter of 1200 nm and 176 nm, respectively. Al dopant is then introduced to the zno nanorods by dipping technique. To start, a broad range of al dopant concentrations (10 mm - 70 mm) at fixed doping duration of 100 s was investigated. The average height of zno nanorods decreased with increasing concentration of al due to the acidity of the doping solution. As a result, only zno doped with 10 mm concentration showed random lasing emission at a threshold of 17.83 mj/cm2 with a spectral width of 1.66 nm. Based on these results, doping duration (0 s to 80 s) was varied for a fixed concentration of 10 mm. A gradual increase of al % was observed and the average zno nanorods diameter did not change significantly with increasing doping duration (± 14 nm). All samples showed random lasing emission and zno nanorods doped for 40 s with 1.19 % of al showed lowest lasing threshold of 12.48 mj/cm2 with a spectral width of 1.76 nm. Finally, thermal laser nano-sensing were investigated. Zno nanorods doped for 60 s revealed a sensitivity as low as 0.001 c-1. In conclusion, zno doped for 40 s showed the best random lasing threshold and zno doped for 60 s showed the best sensing properties due to a narrower linewidth.